Development of a magnetic biocatalyst useful for the synthesis of ethyloleate - Nicolás, Paula (2014)
Candida antarctica Lipase B was successfully immobilized on magnetite (Fe3O4) nanoparticles functionalized with chitosan and glutaraldehyde. The obtained magnetic catalyst was characterized and its performance was evaluated in solvent-free synthesis of ethyl oleate at room temperature. The performance of this biocatalyst was compared with the commercial Novozym 435, as a tool to estimate the efficiency of immobilization. It was found that using 33 mg of the biocatalyst it was possible to reach almost the same activity that was obtained using 12 mg of Novozym 435. Furthermore, this new biocatalyst presents the advantages of not being degraded by short alcohols, being easily recovered from the reaction media by magnetic decantation, and low fabrication cost. The possibility of reutilization was also studied, keeping a significant activity up to eight cycles. A special sampling protocol was also developed for the multiphasic reaction system, to assure accurate results. This novel biocatalyst is an interesting alternative for potential industrial applications, considering the above-mentioned advantages.